Biocompatible space-charged electret material having antibacterial and antiviral effects and its manufacturing method
Patent Information
- Application Number
- JP2024549186
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-01-31
- Publication Date
- 2025-03-26
Smart Images

Figure 2025508448000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is related to U.S. Provisional Patent Application No. 63 / 203,763, filed July 30, 2021, which is incorporated herein in its entirety. This application is also related to U.S. Provisional Patent Application No. 63 / 260,146, filed August 11, 2021, which is incorporated herein in its entirety. This application is also related to U.S. Provisional Patent Application No. 63 / 260,692, filed August 29, 2021, which is incorporated herein in its entirety. This application is also related to U.S. Provisional Patent Application No. 63 / 268,201, filed February 18, 2022, which is incorporated herein in its entirety. This application is also related to U.S. Provisional Patent Application No. 63 / 364,113, filed May 4, 2022, which is incorporated herein in its entirety.
[0002] The present disclosure relates to the field of antibacterial, antiviral, bactericidal and virucidal materials and methods, in particular to space-charged electret polymers having antibacterial, antiviral, bactericidal and virucidal effects and their use in the preparation of antibacterial, antiviral, bactericidal and virucidal materials. [Background technology]
[0003] Microorganisms (e.g., bacteria, viruses and fungi) are ubiquitous in nature and in social environments around the world. They are natural decomposers and play various important roles in the Earth's ecosystems. Some of them are essential for important physiological activities in plants and animals, while some can cause different types of diseases. The development of antibacterial, antiviral, bactericidal and / or virucidal materials is of great importance to save lives and protect people from harmful microbial infections. With the increasing frequency of new deadly viruses (e.g., Ebola, Swine Flu, Avian Flu, Covid-19) and the concomitant emergence of resistant strains (e.g., Methicillin-Resistant Staphylococcus aureus or MRSA), it is urgent and urgent to find new materials and methods for disinfection and microbial eradication to aid in the ongoing fight against bacteria and viruses. Summary of the Invention [Means for solving the problem]
[0004] The present disclosure proposes and provides antimicrobial compositions that have surprisingly effective antibacterial, antiviral, bactericidal and virucidal properties. The compositions include a space charge electret material combined with a hydrophobic material. In selected embodiments, the compositions are highly effective, biocompatible and environmentally friendly.
[0005] The present disclosure also provides a new method for capturing and killing microorganisms (e.g., bacteria and viruses) using space charge electret materials, which includes the steps of contact charging, non-contact electrostatic interaction, and interfacial lipophilicity. In some embodiments, interfacial lipophilicity does not refer to mere contact destruction, which is determined by amphiphilicity and hydrophobicity. Another embodiment provides a method for identifying biocompatible space charge electret materials with effective antibacterial, antiviral, bactericidal, and / or virucidal properties based on a matched cationic polymer and a textile substrate.
[0006] positive charge density The space charge electret material of the present disclosure has a high surface positive charge density. The present disclosure demonstrates that space charge electret materials with high positive charge density have increased antibacterial, antiviral, bactericidal and virucidal effects, for example, as shown in Figures 9-15. In some embodiments, the positive charge density of the space charge electret material is 9.59 nC cm -2 It is.
[0007] Some embodiments have a capacitance of 2 to 35 nC cm -2 surface positive charge density of 6×10 within a frequency range of 80 kHz -7 sm -1 Space charge electret materials with a conductivity of less than 50 mN m -1 The present invention provides a composition comprising a hydrophobic material having a surface energy of less than 100 nm.
[0008] The high positive charge density of the space charge electret material plays a major role in both capturing and killing microorganisms (e.g., bacteria and viruses). First, it attracts biohazards with negatively charged proteins through non-contact electrostatic interactions, which contributes to an increase in collision frequency. Then, contact charging occurs when floating negatively charged biohazards collide with a positively charged electret, resulting in a sudden change in electrostatic potential and a sudden increase in electric stress. The strong electrostatic field firmly anchors the biohazard to the positively charged surface, and the generated non-uniform electric stress contributes to the shearing of the main viral or microbial proteins of the biohazard. In a preferred embodiment of the present invention, the high positive charge density of the space charge electret material is uniform or substantially uniform over the entire surface area of the material.
[0009] Space Charge Electret Materials In some embodiments, the space charge electret material comprises one or more cationic polymers, such as gelatin, chitosan, cationic peptides, cationic cyclodextrins, cationic dextran, cationic cellulose, polyethyleneimine, polylysine, polyamidoamine, poly(amino-co-esters) and poly[2-(N,N-dimethylamino)ethyl methacrylate]. The cationic polymers may be natural, semi-synthetic and / or synthetic, and the polymer structures may be linear, branched, hyperbranched and / or dendritic. The placement of the cationic carrying groups may be either in the backbone or in the side chains.
[0010] Cationic polymers are advantageous and useful because they can kill bacteria with their unique cationic molecular structure without releasing any chemicals. Their mode of antibacterial action is mainly by disrupting microbial cell membranes on contact. The degree of antibacterial activity of cationic polymers is determined by two factors: amphiphilicity and hydrophobicity.
[0011] Exemplary materials for textile substrates include, but are not limited to, natural cotton, wool, cellulose, synthetic polyester, nylon, and / or blends thereof. The construction of textile substrates can be knitted, woven, and non-woven. Some embodiments include blended textiles composed of both hydrophilic natural fibers and hydrophobic synthetic fibers.
[0012] The space charge electret materials of the present disclosure have both high positive charge density and favorable hydrophobicity, making them particularly effective antibacterial, antiviral, bactericidal and virucidal properties. During intimate contact, the hydrophobicity of the space charge electret materials aids in the insertion of lipophilic compartments into the cell membrane of microorganisms via van der Waals interactions, contributing to easier and more rapid destruction of biological hazards.
[0013] In some embodiments, the high positive charge density is greater than 9.59 nC cm -2 As shown in Figures 9-11 and 13, a high positive charge density (e.g., 9.59 nC cm -2) and suitable wettability (surface energy is 20-61 mJ m -2 or mN m -1 The space charge electret material having a molecular weight of 1.0 to 1.5 μg / cm2 has excellent antibacterial, antiviral, bactericidal and virucidal effects against Staphylococcus aureus, SARS-229E, SARS-CoV-2 and Coxsackievirus B6 with an efficacy of over 98% in 5 minutes.
[0014] How to measure space charge density Another embodiment provides a method for identifying compositions with surprisingly effective antimicrobial properties by measuring the electrostatic charge of a space charge electret material and evaluating the contact electrification performance of the material. The positive charge density is used to quantitatively evaluate the degree of contact electrification.
[0015] One exemplary method for measuring the positive charge density of space charge electret materials involves a dual layer device consisting primarily of a lower acrylic plate to which a 6 cm x 6 cm adhesive electrode layer is attached and an upper acrylic plate to which a reference material / electrode layer of the same size is attached. A polytetrafluoroethylene (PTFE) film is attached as the reference material.
[0016] Advantageous properties The compositions of the present disclosure have several significant advantages over current methods.
[0017] Current methods for disinfection have different drawbacks. Chemical disinfectants and sanitizers often induce irritation / toxicity to skin, mucous membranes and respiratory system, and most are not biofriendly to humans in direct and / or long-term wear / contact situations, such as personal protective equipment masks and clothing. In addition, they are also not suitable for air purification systems with long-term disinfection and sterilization effects due to easy evaporation or sweeping caused by low molecular weight and low surface adhesion.
[0018] Metal ions (e.g., mercury, silver, copper, brass, bronze, tin, iron, lead and bismuth ions) are another type of antimicrobial agent that can kill or inhibit the growth of microorganisms based on the trace effect. However, even the mere release of these metal ions can be lethal to humans and harmful to the environment. A less invasive and less toxic method is to dope / incorporate the desired metal ions into other materials (e.g., polymers) in the form of nanoparticles, fibers, coatings or films. Although not easily removed by simple sweeping, due to the high surface energy of metals, they are usually covered with low surface energy materials, which results in a low antibacterial effect.
[0019] In contrast, disclosed herein is a highly effective, biocompatible, environmentally friendly material that can effectively kill microorganisms and can be used directly and for extended wear and contact.
[0020] Woven fabric substrates treated with space charge electret materials are effective in preventing viruses and bacteria from penetrating through fabric filters. The viral and bacterial filtration effectiveness of cellulose / polyester fabrics treated with BPEI space charge electret materials has been demonstrated to be greater than 99.9%.
[0021] The antibacterial, antiviral, bactericidal and virucidal space charge electret material also has excellent biocompatibility by controlling the composition of the material. There was no difference in VERO cell proliferation between untreated and BPEI space charge electret material treated fabrics. Washing from control and space charge electret material treated fabrics moderately reduced VERO E6 cell proliferation. There was no difference in VERO cell proliferation between untreated and C-polar treated fabrics, and no reduction in cell susceptibility was found. These results demonstrate that the space charge electret material is safe and suitable for industrial production and large-scale use.
[0022] In cationic polymers, the hydrophilic cationic carrying groups contribute to attracting the negatively charged membrane via electrostatic attraction, while the hydrophobic alkyl chains aid in the insertion of the cationic polymer chains into the membrane via hydrophobic and van der Waals interactions. The degree of hydrophobicity determines the extent to which the alkyl segments penetrate the lipid bilayer and destroy bacteria. Thus, different cationic polymers have different levels of antibacterial activity. However, highly effective quantification techniques to evaluate the degree of antibacterial activity of cationic polymers are still lacking. Moreover, there is currently little literature on the antiviral and virucidal effects of cationic polymers, especially against COVID-19.
[0023] Use of Space Charge Electret Materials Space charge electret materials can be widely used for air filtration products (e.g., masks, protective clothing and air purifiers), as well as personal / household cleaning and sanitary products, such as hand sanitizers, wet tissues and toilet paper, household / hotel textile products, and related disposable products. Space charge electrets can help block the spread of viruses in people with high filtration efficiency (passive function) and self-disinfection (active function), and can be used without the concern of inducing collateral environmental pollution or indirect / secondary collateral harmful substances. [Brief description of the drawings]
[0024] [Figure 1] 1 illustrates a schematic of the disinfection mechanism of a space charge electret material having a high positive charge density. [Diagram 2] 1 shows the chemical structures of cationic polymers used in the preparation of space charge electret materials and their positive charge state. [Diagram 3] 1 illustrates the surface modification of a textile substrate with a high positive charge density space charge electret material. [Figure 4] 1 illustrates the air filtration and self-disinfecting functions of textile substrate surfaces modified with space charge electret materials. [Diagram 5]1 is a flow chart of surface modification of a textile substrate with BPEI space charge electret as an example. [Figure 6] 1 illustrates generally a charge measurement device for evaluating the positive charging performance of space charge electret materials, as well as a typical charge curve resulting from controlled repeated contact and separation with repeated application and release of an external force. [Figure 7] 1 shows the effect of BPEI concentration on the charge density of BPEI modified fabrics. [Figure 8] 13A-13C typically show the instantaneous output voltage generated when a textile surface modified with a high positive charge density space charge electret material is subjected to repeated impacts / contacts. [Figure 9] 1 shows the virucidal performance of different textile substrates treated with different solution concentrations of BPEI space charge electret material. [Figure 10] 1 shows the results of testing different materials to kill human coronavirus 229E, including tissue, FFP2 filters, FFP2 sponges, Curie spunlace (i.e., a cellulose / polyester fabric treated with BPEI space charge electret material) and Curie paper (i.e., tissue treated with BPEI space charge electret material). [Figure 11] 1 shows the results of testing different materials to kill Coxsackievirus B6, including tissue, FFP2 filters, FFP2 sponges, Curie spunlace (i.e., a cellulose / polyester fabric treated with BPEI space charge electret material) and Curie paper (i.e., tissue treated with BPEI space charge electret material). [Figure 12] We show that cellulose / polyester fabrics treated with BPEI space charge electret material achieve viral filtration effectiveness of greater than 99.9%. [Figure 13] We show that cellulose / polyester fabrics treated with BPEI space charge electret material kill Staphylococcus aureus with greater than 99.9% efficacy. [Figure 14]Test results for Staphylococcus aureus kill of different textile substrates treated with BPEI space charge electret material before and after 60 washes are shown: 100% plain cotton, 100% cotton after 60 washes, polyester / cotton (65% / 35%), polyester / cotton (65% / 35%) after 60 washes, polyester / spandex (92% / 8%), and polyester / spandex (92% / 8%) after 60 washes are shown with sample numbers #1, #2, #3, #4, #5, and #6, respectively. [Figure 15] We show that cellulose / polyester fabrics treated with BPEI space charge electret material achieve bacterial filtration effectiveness of greater than 99.9%. [Figure 16] FIG. 1 shows the effect of cellulose fabrics treated with different concentrations of BPEI space charge electret material on the viability of VERO E6 cells. [Figure 17] FIG. 1 shows the effect of cellulose / polyester fabrics treated with different concentrations of BPEI space charge electret material on the viability of VERO E6 cells. [Figure 18] 1 shows the results of testing the cytotoxicity of different concentrations of BPEI space charge electret material (C-POLAR) against GMK cells (left panel) and MRC5 cells (right panel). [Figure 19] FIG. 1 shows the effect of cellulose fabrics treated with different BPEI space charge electret materials on cell sensitivity. [Figure 20] FIG. 1 shows the effect of cellulose / polyester fabrics treated with different BPEI space charge electret materials on cell sensitivity. [Figure 21A] 1 shows ISO 10993-5 (test for in vitro cytotoxicity) test results for textile substrates treated with BPEI space charge electret material. [Figure 21B] 1 shows ISO 10993-10 (animal skin irritation test) test results for textile substrates treated with BPEI space charge electret material. [Figure 21C]1 shows the results of ISO 10993-10 (skin sensitization test) testing on textile substrates treated with BPEI space charge electret material. [Figure 22] A method for loading space charge electret material onto the surface of a textile substrate material is shown. [Figure 23] FIG. 1 is a general flow chart and preferred embodiment for the design and fabrication of space charge electret materials with high charge density based on cationic polymers for a wide range of antibacterial, antiviral, bactericidal and virucidal applications. [Figure 24A] 1 illustrates a schematic illustrating hydrogen bonding between linear PEI and a fiber substrate (an example of a hydrophobic material) according to a preferred embodiment. [Figure 24B] 1 illustrates a schematic illustrating hydrogen bonding between branched PEI and a fiber substrate (an example of a hydrophobic material) according to a preferred embodiment. [Figure 25A] According to an exemplary embodiment, a mechanism is illustrated in which three silyl linkers are attached to a fiber substrate (an example of a hydrophobic material), attached to each other via a single -O-linker, and then attached to linear PEI via epoxide ring opening. [Figure 25B] According to an exemplary embodiment, a mechanism is illustrated in which three silyl linkers are attached to a fiber substrate (an exemplary hydrophobic material), attached to each other via a single -O-linker, and then attached to a branched PEI via epoxide ring opening. [Figure 26A] 1 illustrates generally the process steps for attaching cationic polymers of the present disclosure to textiles / fibers (i.e., fibrous substrate materials) according to exemplary embodiments. [Figure 26B] FIG. 1 shows an exemplary schematic diagram of bonding a cationic polymer to a fibrous substrate material according to an exemplary embodiment. [Figure 27A] 1 shows exemplary synthetic routes to make various silylated linear PEI compounds via silylation of linear PEI according to exemplary embodiments. [Figure 27B] 1 shows exemplary synthetic routes to make various silylated branched PEI compounds via silylation of branched PEI according to exemplary embodiments. [Figure 27C] 1 shows a synthetic route for reacting silylated linear PEI with a fiber substrate (an exemplary hydrophobic material) according to an exemplary embodiment. [Figure 27D] 1 shows a synthetic route for reacting silylated branched PEI with a fiber substrate (an exemplary hydrophobic material) according to an exemplary embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The present application is described in detail below with drawings and specific embodiments to enable those skilled in the art to make and use various embodiments. Descriptions of specific devices, techniques and applications are provided as examples. Various modifications to the examples described herein will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other examples and applications without departing from the spirit and scope of the present invention. Thus, the disclosed invention is not intended to be limited to the examples described herein, but is to be accorded the full breadth and scope of the claims.
[0026] definition Unless otherwise defined, all technical and scientific terms used herein have the same plain meaning as commonly understood by those skilled in the art of this application. The terms used in the description of this application are only for the purpose of describing or explaining certain embodiments and are not intended to limit the application. As used herein, the term "and / or" includes any combination of one or more of the associated listed items.
[0027] Furthermore, the technical features referred to in the various embodiments of the present application described below can be combined with each other unless they contradict or conflict with each other.
[0028] As used herein, "electret" (the word is formed from electr- from "electricity" and -et from "magnet") refers to a dielectric material that has a semi-permanent macroscopic electric field at its surface. Two distinct material classes can be separated: dipole electrets and space charge electrets. Dipole electrets are composed of electric dipoles that are typically electrically neutral overall in other circumstances, but can result in a macroscopic semi-permanent electric field after alignment of the dipoles by an external force (e.g., high voltage polarization). Materials that have a macroscopic net electrostatic charge are defined as space charge electrets, which can be easily generated by contact electrification. They have a semi-permanent electric field due to the charge-unbalanced surface. Electrets can be made by first melting a suitable dielectric material, for example a polymer or wax containing polar molecules, and then resolidifying it in a strong electrostatic field. The polar molecules of the dielectric align themselves in the direction of the electrostatic field, resulting in a dipole electret with a permanent electrostatic deflection. Any factor that disturbs the alignment of the polar molecules results in a reduction in the electrostatic field, e.g., high temperature. Electrets can also be made by embedding excess charge into highly insulating dielectrics, e.g., by electron beam, corona discharge, jet from an electron gun, electrical breakdown of a gap, or dielectric barrier.
[0029] The space charge electret material of the present invention, which has antibacterial, antiviral, bactericidal and virucidal effects, has high positive charge density, amphiphilicity and biocompatibility. In some embodiments, the space charge electret material comprises one or more cationic polymers. In certain preferred embodiments, the space charge electret material comprising one or more cationic polymers comprises (C-POLAR) linear polyethyleneimine (PEI) and / or branched polyethyleneimine (BPEI). In some embodiments, the space charge electret material does not align molecular poles or embed excess charge. In some embodiments, the space charge electret material or cationic polymer has a net electrostatic charge due to the different numbers of cationic and anionic charges. In some embodiments, the electric field of the space charge electret material can be further enhanced by contact charging due to the easy transfer of ionic groups. In other embodiments, the space charge electret material has amphiphilicity. In some embodiments, the space charge electret material has hydrophilic cationic carrying groups and long hydrophobic alkyl chains.
[0030] As used herein, the term "space charge density" or "charge density" refers to the amount of charge per unit surface area or unit contact area. The term "positive space charge density" or "positive charge density" refers to the total amount of positive charges minus negative charges per unit surface area or unit contact area.
[0031] As used herein, the term "conductivity" or "electrical conductivity" refers to the ability of a material to resist electric current. In some embodiments, conductivity increases at low frequencies. In some embodiments, conductivity decreases at high frequencies.
[0032] As used herein, the term "resistivity" or "electrical resistivity" refers to the ability of a material to conduct electric current. It is the opposite of the conductivity or electrical conductivity of a material.
[0033] As used herein, the term "surface energy" refers to the excess energy associated with the existence of a surface.
[0034] As used herein, the term "hydrophobic material" refers to a material that contains at least one hydroxyl group on its surface that can react with an amino group. The hydroxyl group can be part of the molecular structure itself (e.g., in the case of polyvinyl alcohol and its derivative copolymers), or the hydroxyl group can come from a water molecule that has been adsorbed to the surface of the material, for example, by atmospheric moisture. Most surfaces, regardless of their inherent hydrophobicity, have a thin film of water attached to the surface. -1 Even hydrophobic materials with solid surface energies of less than 28 mN m (e.g., PTFE and poly(tetrafluoroethylene-cohexafluoropropylene) (FEP)) can adsorb approximately 1.5-2.0 monolayers of water on their surfaces. In some embodiments, the hydrophobic material is a synthetic polymer. In some embodiments, the hydrophobic material is a synthetic polymer with at least one hydroxyl group. In some embodiments, the synthetic polymer has a high hydrophobic surface and contains few hydroxyl groups. In some embodiments, the synthetic polymer has a high hydrophobic surface and contains few hydroxyl groups. In some embodiments, the synthetic polymer has a high hydrophobic surface and contains less than 28-48 mN m -1 has a solid surface energy of
[0035] In some embodiments, the amino group is part of the silyl linker of the present disclosure. Hydrophobicity can be measured by methods known to those skilled in the art, for example, by measuring the contact angle of a liquid drop on the surface of the material or calculating the solid surface energy. In some embodiments, the hydrophobic material is a synthetic or natural polymer. Examples of synthetic polymers include, but are not limited to, polyethylene (PE), polypropylene (PP) and polyethylene terephthalate (PET). In some embodiments, the hydrophobic material comprises a natural polymer cellulose fiber or fabric containing hydroxyl groups. In some embodiments, the hydrophobic material is a mixture of synthetic and natural polymers with suitable surface wettability. The surface wettability of the substrate can be adjusted by blending synthetic and natural polymer fibers. Examples of hydrophobic materials include, but are not limited to, cotton, linen, silk, wool, spunlace, chitosan, polyvinyl alcohol, polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), acrylonitrile-butadiene-styrene (ABS), poly(methyl methacrylate) (PMMA), aramids (e.g., nylon), silicones (e.g., polydimethylsiloxane), latex, glass, semi-fluorinated polymers, and perfluorinated polymers (e.g., polytetrafluoroethylene (PTFE)). In other embodiments, the hydrophobic material is a polyester. A "polyester" is a polymer that contains an ester functional group in every repeat unit of the backbone. Examples include, but are not limited to, polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).
[0036] In some embodiments, the hydrophobic material is depicted with one or more hydroxyl groups as shown below: In some embodiments, the hydrophobic material is a fibrous substrate material. The fibrous substrate material is any material that includes cellulose fibers.
[0037] [ka]
[0038] Those skilled in the art will appreciate that the schematic diagram above is not intended to show that the hydrophobic material / fibrous substrate has only three -OH groups. Instead, the drawing is merely illustrative and is intended to encompass many -OH groups, the number being dictated by the nature of the material.
[0039] As used herein, the term "C-POLAR" or "c-polar" refers to a positively charged / cationic polymer that can be applied to the surface of a hydrophobic material, for example, a spunlace surface, a cotton surface, or a polyester surface. In some embodiments, "C-POLAR" or "c-polar" refers to an electret material (agent or solution) used for surface modification of a textile substrate. In some embodiments, "C-POLAR" or "c-polar" is polyethyleneimine (PEI), and in some embodiments, "C-POLAR" or "c-polar" is linear polyethyleneimine. In some embodiments, "C-POLAR" or "c-polar" is branched polyethyleneimine (BPEI). In some embodiments, "C-POLAR" or "c-polar" refers to a concentration range of PEI or BPEI. In some embodiments, "C-POLAR" or "c-polar" is 2-30% PEI or BPEI, 2-15% PEI or BPEI, 2-10% PEI or BPEI, 2-8% PEI or BPEI, 2-4% PEI or BPEI, 4-6% PEI or BPEI, 6-8% PEI or BPEI, 2%, 3%, 4%, 5%, 6%, 7% or 8% PEI or BPEI. In some embodiments, "C-POLAR" or "c-polar" is 2%, 4%, 6%, 8% or 10% PEI or BPEI. In some embodiments, "C-POLAR" or "c-polar" is a space charge electret material. For clarity, when "C-POLAR" or "c-polar" is described together with a fabric, for example "C-POLAR spunlace", it refers to a composition including a cationic polymer and a fabric.
[0040] As used herein and in the claims, the term "antimicrobial composition" refers to a composition that is effective (i.e., in a suitable form and amount) to kill or inhibit the growth of microorganisms. In some embodiments, the antimicrobial composition is one or more space charge electret materials. In some embodiments, the antimicrobial composition is one or more cationic polymers. In some embodiments, the antimicrobial composition comprises C-POLAR or BPEI. In some embodiments, the antimicrobial composition comprises cotton and / or polyester.
[0041] As used in this specification and in the claims, the terms "comprising" (or any related form, e.g., "comprise" or "comprises"), "including" (or any related form, e.g., "include" or "includes"), and "containing" (or any related form, e.g., "contain" or "contains") imply the inclusion of the subsequent element but not the exclusion of other elements. In any embodiment where the terms "comprising" (or any related form, e.g., "comprise" or "comprises"), "including" (or any related form, e.g., "include" or "includes"), or "containing" (or any related form, e.g., "contain" or "contains") are used, it is understood that the present disclosure / application also includes alternative embodiments in which the terms "comprising", "including" or "containing" are replaced with "consisting essentially of" or "consisting of". It is understood that these alternative embodiments using "consisting of" or "consisting essentially of" are narrower embodiments than the "comprising", "including" or "containing" embodiments.
[0042] As used herein, the singular forms "a," "an," and "the" are intended to include the plural forms unless the context clearly dictates otherwise. When ranges are referenced in the specification, it is understood that the range includes each separate point within the range. For example, 1-7 means 1, 2, 3, 4, 5, 6, and 7.
[0043] As used herein, the term "about" is understood to be within the normal tolerance range in the art, being no more than ±10% of the stated value. By way of example only, about 50 means 45 to 55, including all values therebetween. As used herein, the term "about" a particular value also includes the particular value, for example, about 50 includes 50.
[0044] As used herein, the term "cationic polymer" refers to a macromolecule having cationic groups on the polymer backbone and / or side chains, such as cationic peptides, (quaternary) ammonium salts, biguanidines, phosphonium salts, guanidines, sulfonium and pyridinium salts. In some embodiments, the cationic polymer carries a macroscopic positive charge and provides a permanent macroscopic electric field to the surface. In some embodiments, the cationic polymer is a type of space charge electret material. In certain preferred embodiments, the cationic polymer comprises (C-POLAR) linear polyethyleneimine (PEI) and / or branched polyethyleneimine (BPEI).
[0045] As used herein, the term "amphiphilic" refers to the state of a molecule having both hydrophilic and hydrophobic regions, e.g. (in the case of cationic polymers) hydrophilic cationic carrying groups and long hydrophobic alkyl chains.
[0046] antimicrobial composition One embodiment of the present disclosure is 2 to 35 nC cm -2 surface positive charge density of 6×10 within a frequency range of 80 kHz -7 sm -1 Space charge electret materials with a conductivity of less than 50 mN m -1 or mJ m -2 The present invention provides an antimicrobial composition comprising a hydrophobic material having a surface energy of less than 100 nm.
[0047] In some embodiments, the surface positive charge density is between 5 and 10 nC cm -2 , 10~20nC cm -2, 5.5nC cm -2 or greater than 9.59 nC cm -2 It's super.
[0048] In some embodiments, the space charge electret material has a 6 It has a resistivity greater than Ω·m.
[0049] According to another embodiment of the present disclosure, the space charge electret material is a cationic polymer. In some embodiments, the cationic polymer is natural, semi-synthetic or synthetic, the cationic polymer has a linear, branched, hyperbranched or dendritic structure, and the cationic polymer comprises at least one cationic carrying group located on the backbone or side chain of the polymer. In other embodiments, the cationic polymer is selected from the group consisting of gelatin, chitosan, cationic peptides, cationic cyclodextrin, cationic dextran, cationic cellulose, polyethyleneimine (including linear polyethyleneimine and / or branched polyethyleneimine), polylysine, polyamidoamine, poly(amino-co-ester) and poly[2-(N,N-dimethylamino)ethyl methacrylate]. In yet other embodiments, the polymer is selected from those listed in Figure 2 herein.
[0050] According to another aspect of the present disclosure, the surface of the hydrophobic material comprises a cellulose structure having at least two components, at least one of which is slightly positively charged in polarity. In some embodiments, at least one of the at least two components has a hydrophobicity of 50 mN m -1 In some embodiments, the surface of the hydrophobic material is dense, flat, uniform and uniformly positively charged.
[0051] Linker In some embodiments, the cationic polymer is attached to the hydrophobic material via a linker molecule. 20 an aliphatic chain, where C1-C 200, 1, 2 or 3 carbon units of the aliphatic chain are replaced with one or more heteroatoms selected from the group consisting of -O-, -S- and -NR-, where R is independently H or C1-C6 alkyl, and C1-C6 alkyl is 20 At least one carbon unit of the aliphatic chain is bonded to a silyl group. In some embodiments, the silyl group is -Si(OR + )2, -Si(R + )2 or -Si(R + )(OR + ), where each R + is independently selected from the group consisting of H and C1-C6 alkyl, or R + is a silyl group of another linker, and the silyl groups of the two different linkers are joined via a single -O- group. + are independently H or C1-C3 alkyl.
[0052] As an example, the illustration below shows how three silyl linkers are attached to a hydrophobic material and to each other via a single -O-linker.
[0053] [ka]
[0054] Si-C Linker According to another embodiment, the silyl group is bonded to a carbon atom of the linker. In some embodiments, the carbon atom is the terminal carbon unit of the linker. The terminal carbon unit is the carbon unit of the aliphatic chain that is bonded to only one other unit in the aliphatic chain. For example, in the C4 carbon chain CH3CH2CH2CH3, the terminal carbon units are the first and fourth carbon atoms.
[0055] Si-N Linker In some embodiments, the silyl group is attached to a nitrogen atom of the linker. 20An aliphatic group, where one, two or three carbon units of the linker are replaced with -NR-, -N=, or -N(R)2, where each R is independently H or C1-C6 alkyl.
[0056] One of ordinary skill in the art will understand which nitrogen groups are suitable replacements for carbon groups based on the number of valence groups of the carbon group being replaced. For example, the aliphatic group CH3CH2CH = In CHCH2CH3, the first carbon atom is -N(R) 2, and the second carbon atom is replaced with -NR-, while the third carbon atom is replaced with -N=.
[0057] In some embodiments, the linker, together with the cationic polymer, is: [ka]
[0058] In the formula, R 0 is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and n is 0, 1, 2, 3 or 4. In some embodiments, n is >0. In some embodiments, n is 1, 2, 3, 4, 5, 6, 7, or 8. In some embodiments, n is >0 to <100. In some embodiments, n is 0 to 10, 0 to 20, 0 to 30, 0 to 40, or 0 to 50. In some embodiments, n is 1 to 20.
[0059] Linker + Cationic Polymer Example 1 is an additional exemplary embodiment of a linker together with a cationic polymer.
[0060] [ka] TIFF2025508448000006.tif164155
[0061] Other Linkers According to another embodiment, the linker is C7-C 10 aliphatic, where one of the carbon units of the linker is replaced with -O-. In some embodiments, the linker is optionally substituted with one or more of the J group, where J is OR 0 , S.R. 0 or N(R 0 )2, and R 0 is H or C1-C6 alkyl. In certain exemplary embodiments, the linker is -Si(OR + )2-(CH2)3OCH2CH(OR 0 )CH2-.
[0062] In another exemplary embodiment, the linker is -Si(OR + )2. In yet other exemplary embodiments, the silyl group is covalently bonded to a hydroxyl group of the hydrophobic material.
[0063] Method for modifying the surface of a hydrophobic material Another aspect of the present disclosure is a method for modifying a surface of a hydrophobic material with a space charge electret material, comprising the steps of: (a) dissolving a space charge electret material in a suitable solvent; (b) introducing the space charge electret material / suitable solvent mixture onto the surface of the hydrophobic material by dip coating and / or spraying; (c) removing the suitable solvent by tensioning methods and / or air drying or temperature drying; and (d) optionally performing one or more systematic tests and evaluations on the surface of the hydrophobic material by contact charging performance evaluation, antiviral test, antibacterial test, viral filtration test, and / or bacterial filtration test; The present invention provides a method comprising:
[0064] Another aspect of a preferred embodiment of the present disclosure is a method for modifying a surface of a hydrophobic material, comprising the steps of: (a) dissolving a space charge electret material in a suitable solvent to form a space charge electret material / suitable solvent mixture; (b) introducing the space charge electret material / suitable solvent mixture onto the surface of the hydrophobic material by dip coating and / or spraying; (c) subjecting the hydrophobic material to a tension forming process and / or drying the material at ambient or elevated drying temperatures; and (d) optionally performing one or more systematic tests and evaluations on the surface of the hydrophobic material by contact charging performance evaluation, antiviral test, antibacterial test, viral filtration test, and / or bacterial filtration test; The method includes:
[0065] In some embodiments, the space charge electret material is branched polyethyleneimine (BPEI), linear polyethyleneimine (LPEI or PEI), dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, cationic cellulose, didecyldimethylammonium chloride, or combinations thereof.
[0066] In some embodiments, the space charge electret material is LEI or BPEI.
[0067] In some embodiments, the concentration of the space charge electret material in a suitable solvent is between 0.195% and 10%.
[0068] In some embodiments, the preferred solvent is water, ethanol, or a mixture thereof. In some embodiments, the preferred solvent is water. In selected preferred embodiments, the space charge electret material is dissolved in a solvent that does not contain added salt. In some embodiments, the hydrophobic material is cellulose or a cellulose / polyester nonwoven fabric.
[0069] In some embodiments, a tension forming method is applied, which includes one or more of the following actions: stretching, steaming, heating, applying pressure, or applying pressure to the material, including high pressure air flow or mechanical pressure. In some preferred embodiments, pressure is applied to the material by adjustable rollers. In some preferred embodiments, heating is provided by an oven.
[0070] In some embodiments, the drying temperature is less than 100° C. In some embodiments, the drying temperature is less than 50° C. o C~100 o C, 100 o C~200 o C, 150 o C~200 o C, 150 o C~175 o C, 175 o C~200 o C, 150 o C~170 o C or 155 o C~165 o C. In some preferred embodiments, the drying temperature is 160° C.
[0071] In some embodiments, the one or more systematic tests and evaluations are contact charging performance evaluations, antiviral tests, antibacterial tests, viral filtration tests, bacterial filtration tests, or combinations thereof.
[0072] Method for loading space charge electret material Another aspect of the present disclosure is a method for loading a space charge electret material onto a surface of a hydrophobic material, comprising the steps of: (a) carding at least one of the at least two components to form a drylaid web; (b) loading a space charge electret material onto the fabric surface of the dry web by a high pressure liquid stream; and (c) drying the dry web so that the space charge electret material forms bridges with the fabric surface and winding it up to form a surface of hydrophobic material; The present invention provides a method comprising:
[0073] In some embodiments, the hydrophobic material comprises textile fibers that are knitted, woven, nonwoven, or a mixture thereof. In some embodiments, the textile fibers comprise both hydrophilic natural fibers and hydrophobic synthetic fibers (e.g., blended fibers). In some embodiments, the textile fibers comprise cotton, wool, cellulose, spunlace, synthetic polyester, polypropylene, polyethylene, nylon, or a blend of at least two thereof. In some embodiments, at least one component is cotton or polyester. In some embodiments, the other component is cotton or polyester, provided that the two components are not identical. In some embodiments, the ratio of the two components is 65% polyester / 35% cotton, or 50% polyester / 50% cotton.
[0074] In some embodiments, the cationic polymer comprises 0.195% to 15% by weight of the total antimicrobial composition.
[0075] Methods for preparing linker compositions Some embodiments of the present disclosure provide a method for preparing an antimicrobial composition having a linker molecule, comprising the steps of: a) combining a silylated epoxide compound IIa with a hydrolysis agent in the presence of water to form compound IIb: [ka] [wherein R is independently C1-C6 alkyl] b) heating compound IIb with a hydrophobic material IIc to form compound IId; [ka] c) combining compound IId with a cationic polymer IIe under epoxide ring-opening conditions; [ka] Formula II (shown first below) or II': [ka] TIFF2025508448000011.tif185132[In the formula, each R is independently H or C1-C6 alkyl, or R is a silyl group of another linker; R X is H or another linker The present invention provides a method comprising:
[0076] In some embodiments, another linker is formed via an epoxide ring-opening reaction. In some embodiments, multiple linkers are attached as shown in the diagram below.
[0077] [ka]
[0078] Hydrolytic agents are known to those skilled in the art and may include acids or bases. For clarity, an acid is a molecule that can donate a proton. Examples include hydrochloric acid (HCl), hydroiodic acid (HI), hydrobromic acid (HBr), perchloric acid (HClO4), nitric acid (HNO3) and sulfuric acid (H2SO4). In some embodiments, an acid together with water can hydrolyze a molecule, i.e., replace other groups with water molecules. In other embodiments where the hydrolytic agent is an acid or a base, the weak acids or weak bases defined above also provide examples and provide the following ranges.
[0079] In some embodiments, the hydrolysis agent is "pH adjusted" water. The pH of the water can be adjusted by adding a weak acid (e.g., acetic acid) or a weak base (e.g., ammonia) to carry out the hydrolysis of IIa to IIb. In some embodiments, the concentration range of acetic acid in the water is 0.02% to 1%. In other embodiments, the concentration of ammonia is 0.25 to 3%. In some embodiments, the hydrolysis reaction is carried out at a temperature below 50°C, in some embodiments, 20 to 50°C.
[0080] Epoxide ring-opening conditions are known to those skilled in the art and typically involve the use of Lewis acids, such as trimethylborane, aluminum oxide, and lithium perchlorate. In some embodiments, at least one Lewis acid is added and used as a catalyst to activate the ring-opening of the epoxide with the amino group of another molecule. In some embodiments, the epoxide ring-opening reaction is carried out at a temperature between 60° C. and 150° C. for a period ranging from 5 minutes to 3 hours. Those skilled in the art will be aware that in some embodiments, the epoxide ring-opening reaction can be carried out without the use of Lewis acids. For example, in some embodiments, microwave irradiation is used after treatment to increase the grafting ratio of linear / branched polyethyleneimine on the surface of the modified substrate containing epoxy groups.
[0081] Examples of compounds of formula IIa are shown below.
[0082] [Table 1]
[0083] The cationic polymers described herein contain many amino groups, and the hydrophobic material treated with the epoxy-silyl linker (compound of formula IId) also contains several reactive epoxy sites. Thus, there are many ways that the amino groups of the cationic polymer can react with the hydrophobic material through one or more epoxide ring-opening reactions via the linkers described herein. Sometimes, two amino groups in the same polymer repeat unit of the cationic polymer can react with the epoxide groups of two different silyl linkers to bond with two different hydroxyl groups of the hydrophobic material, as shown in the schematic below.
[0084] [ka]
[0085] One skilled in the art will appreciate that there are numerous ways in which the amino groups of the cationic polymer may react with the various epoxide groups of the compound of formula IId.
[0086] Another embodiment of the invention is a method for preparing an antimicrobial composition having a linker, comprising the steps of: d) hydrolyzing compound IIIa in the presence of water and acid to form compound IIIb: [ka] [wherein R is an aliphatic group], e) hydrolyzing compound IIIb to hydrophobic material IIIc: [ka] by heating with [ka] [In the formula, L 1 and L 2 wherein each is independently H or a silyl group of another linker attached to the same hydrophobic material; The present invention provides a method comprising:
[0087] In some embodiments, the compound of IIIa is [ka] In the formula, R=CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and n is 0, 1, 2, 3 or 4.
[0088] In some embodiments, the compound of IIIa is selected from the compounds of Table IIIa.
[0089] [Table 2]
[0090] In some embodiments, the hydrophobic material IIIc contains multiple hydroxyl (OH) units, and thus there are multiple ways that the hydrolyzed compound IIIb can react with the hydroxyl groups. In some exemplary embodiments, one or more silyl groups can be bonded to each other via an oxygen atom, as shown diagrammatically below.
[0091] [ka]
[0092] Another aspect of the present disclosure is a method of preparing an antimicrobial composition having a linker, comprising the steps of: a) Cationic polymer IVa [ka] with a silylating agent Z-Cl [where: Z is SiR(OR)2, Si(R)2(OR) or Si(OR)3; each R is independently C1-C6 alkyl; Compound IVb, wherein compound IVb is [ka] each R is independently C1-C6 alkyl; b) mixing compound IVb with an acid in the presence of water to produce compound IVc, [ka] each R is independently C1-C6 alkyl; c) dissolving compound IVc in a hydrophobic material IVc [ka] by heating with [ka] forming an antimicrobial composition of The present invention provides a method comprising:
[0093] Another aspect of the present disclosure is a method of preparing an antimicrobial composition having a linker, comprising the steps of: a) Cationic polymer Va [ka] with a silylating agent Z-Cl [where: Z is SiR(OR)2, Si(R)2(OR) or Si(OR)3; each R is independently C1-C6 alkyl; Compound Vb: wherein compound Vb is a compound of formula Va in which one or more nitrogen units are silylated with one or two Z groups; b) mixing compound Vb with an acid in the presence of water to form compound Vc, where compound Vc is a compound of Vb where R is H; c) mixing the compound Vc with a hydrophobic material Vd [ka] TIFF2025508448000028.tif6133 to form the antimicrobial composition of the applicable claims herein; The present invention provides a method comprising:
[0094] Silylating Agent Silylating agents are known to those skilled in the art and are agents that aid in the addition of a silyl group to another molecule. In some embodiments, the silylating agent is Z-Cl, where Z is SiR(OR)2, Si(R)2(OR), or Si(OR)3, and each R is independently a C1-C6 alkyl.
[0095] In some embodiments, each R is independently CH3, CH2CH3, CH2CH2CH3, or CH(CH3)2.
[0096] Exemplary embodiments of antimicrobial compositions with Si linkers are shown in Table V.
[0097] [Table 3] TIFF2025508448000030.tif213140
[0098] In some embodiments, compound IVb is selected from the compounds of Table IV.
[0099] [Table 4] TIFF2025508448000032.tif201153TIFF2025508448000033.tif196153TIFF2025508448000034.tif225151TIFF2025508448000035.tif114152
[0100] Here, each R is independently a C1-C6 alkyl.
[0101] How to Kill Microorganisms Another aspect of the present disclosure includes the provision of a method of killing microorganisms comprising filtering air containing microorganisms through an antimicrobial composition of the present disclosure to produce air that is 95%-99.9% microorganism free. In some preferred embodiments, the air is 99-99.9% microorganism free. In some most preferred embodiments, the air is 99.9% microorganism free.
[0102] In some embodiments, the microorganisms have a mean particle size (MPS) of 1-10 μm. In some embodiments, the microorganisms have an MPS of 1-5 μm. In some embodiments, the microorganisms have an MPS of 3.0±0.3 μm.
[0103] In some embodiments, air moves through the antimicrobial space charge electret material at an air flow rate of at least 20 L / min. In some embodiments, the air flow rate is 20-50 L / min. In some embodiments, the air flow rate is 28.3 L / min.
[0104] In some embodiments, the microorganism is a bacterium or a virus. In some embodiments, the virus is SARS-CoV-2, SARS-229E, Coxsackievirus B6, or influenza. In some embodiments, the bacterium is Staphylococcus aureus.
[0105] Another aspect of the present disclosure provides a method of killing microorganisms, comprising contacting a space charge electret material with the microorganism for an incubation time of at least 1-5 minutes, thereby killing 99.9% of the microorganisms. In some embodiments, the microorganism is a bacterium and the incubation time is at least 1 minute. In some embodiments, the microorganism is a virus and the incubation time is at least 5 minutes. In some embodiments, the virus is SARS-CoV-2, SARS-229E, Coxsackievirus B6 or influenza. In some embodiments, the bacterium is Staphylococcus aureus. For clarity, "contacting" refers to bringing the microorganism into close proximity with the antimicrobial composition such that the high positive charge density space charge electret material captures and kills the microorganism or microbe described herein.
[0106] How to measure space charge density Another aspect of the present disclosure is a method for measuring space charge density of a test material, comprising: (a) placing a test material between a lower acrylic plate containing an adhesive electrode layer and an upper acrylic plate containing a reference material / electrode layer of a charge measuring device, an electrometer being connected to the adhesive electrode layer and the reference material / electrode layer, and the test material being adhered to the adhesive electrode layer; (b) repeatedly mechanically contacting and separating the upper acrylic plate and the lower acrylic plate while repeatedly measuring the charge value with an electrometer to obtain one or more charge curves; (c) calculating a difference in the charge values by subtracting the minimum charge value from the maximum charge value; and (d) determining the space charge density of the test material by dividing the difference in the charge values by the contact area of the test material between both the adhesive electrode layer and the reference material / electrode layer; The present invention provides a method comprising:
[0107] In some embodiments, the reference material is a polytetrafluoroethylene (PTFE) film.
[0108] In some embodiments, the adhesive electrode layer and the reference material / electrode layer have the same size.
[0109] antimicrobial products Another aspect of the present disclosure is to provide an antimicrobial product comprising or incorporating the antimicrobial composition of any of the preceding embodiments. In some embodiments, the antimicrobial product is an air conditioning system, an air conditioning unit, an air purifier, a disinfecting fabric, a disinfecting garment (PPE), a face mask, a reusable disinfecting face mask, an air filter, a HEPA filter, a HEPA filter for electric vehicles, an automatic fabric, an automotive interior material, a disinfecting material, a disinfecting clothing, a disinfecting glove, or a hand sanitizer.
[0110] In some embodiments, the two components of the surface of the hydrophobic material are cotton and cellulose, and the space charge electret material comprises branched / linear polyethyleneimine, chitosan, poly-L-lysine, or poly-D-lysine. In some embodiments, the cellulose is polyester, and the space charge electret material comprises branched polyethyleneimine (BPEI) or linear polyethyleneimine. In some embodiments, the two components of the surface of the hydrophobic material are 50% cotton and 50% polyester, and the space charge electret material comprises one or more of 2%, 3%, 4%, 5%, 6%, 7%, 8%, and 9% branched polyethyleneimine (BPEI) or linear polyethyleneimine. In some embodiments, the two components of the surface of the hydrophobic material are 50% cotton and 50% polyester, and the space charge electret material comprises 8% branched polyethyleneimine (BPEI) or 8% linear polyethyleneimine (PEI). In some embodiments, the antimicrobial composition further comprises 8.7% poly(diallyldimethylammonium chloride), 19.7% polyacrylamide, and / or 3.1% ammonium polyphosphate.
[0111] Exemplary embodiments of the present invention How to Kill Microorganisms Referring to FIG. 1, the main disinfection mechanism of space-charged electret materials with high positive charge density, which capture and kill microorganisms (e.g., bacteria and viruses), is based on the combined and synergistic effects of contact electrification and non-contact electrostatic interactions, in addition to contact destruction determined by amphiphilicity and hydrophobicity. Research carried out by the Weizmann Institute of Science in Israel has shown that the net charge of most proteins, such as microorganisms (bacteria and fungi) and viruses, is negatively charged. These are often in the form of protein envelopes. First, space-charged electret materials with high positive charge density attract biological hazardous materials with negatively charged proteins (e.g., bacteria and viruses) through non-contact electrostatic interactions, resulting in an increase in contact / collision frequency. Then, contact electrification occurs when floating negatively charged biological hazardous materials collide with a positively charged electret, resulting in a sudden change in electrostatic potential and a sudden increase in electric stress. The electrostatic field lines very directionally and strongly seek the negatively charged surface of the biohazardous material away from the highly positively charged surface of the space charge electret material, creating a very non-uniform electric stress on the surface of the biohazardous material. The strong electrostatic field strongly pins the biohazardous material to the positively charged surface, and the generated non-uniform electric stress thereby contributes to the shearing of the envelope proteins and / or other major viral or microbial proteins of the biohazardous material. During close contact, the hydrophobicity of the amphiphilic space charge electret material also aids in the insertion of the lipophilic compartment into the membrane via van der Waals interactions. Thus, the biohazardous material can be captured and killed by the amphiphilic space charge electret material with high positive charge density cleaving the envelope proteins and / or other major microbial proteins of the biohazardous material based on the combined effect of non-contact electrostatic interaction, contact electrification and van der Waals interaction. This new capture and disinfection mechanism mainly uses electric charges (+ / -) and the generated electrostatic field creates a physical barrier and destruction. In this way, no additional energy or chemicals are needed to stop microorganisms or viruses from penetrating the surface.The cationic polymers selected for the space charge electret material are also non-toxic. This barrier can be applied and used in many ways, but one example of how it can be used is the application of the polymer to air filters. When properly implemented, it captures and traps microorganisms and viruses, preventing them from passing through the filter and into the filtered air.
[0112] Space Charge Electret Materials The space charge electret material of the present disclosure is composed of one or more cationic polymers. With reference to FIG. 2, cationic polymers are a type of macromolecule that contains cationic groups, such as linear polyethyleneimine (PEI or LPEI), polylysine (PLS), branched polyethyleneimine (BPEI), chitosan (CS), cationic cellulose (CCL), polyamidoamine (PADAM), poly(amino-co-ester) (PAE) and poly[2-(N,N-dimethylamine)ethyl methacrylate] (PDAMEMA). In some embodiments, the cationic polymers have primary, secondary or tertiary amine functional groups that can be protonated, such as (quaternary) ammonium salts, biguanidine, guanidine and pyridinium salts. In some embodiments, the cationic polymers contain non-amine cationic groups, such as phosphonium salts and sulfonium. The cationic polymers may be natural, semi-synthetic and synthetic, and the polymer structures may be linear, branched, hyperbranched or dendritic. The location of the cationic carrying group can be either in the backbone or in the side chain. In some embodiments, the cationic polymer is gelatin, chitosan, cationic peptide, cationic cyclodextrin or cationic dextran. In some embodiments, the cationic polymer is used in the fabrication of space charge electret materials.
[0113] Different cationic polymers have different positive charge densities. Other embodiments provide compositions with high positive charge density surface space charge electret materials that meet the specific requirements of the target application. The positive charge density plays a major role in the degree of antibacterial and antiviral activity of textile substrates treated with the space charge electret material. In selected preferred embodiments, the space charge electret material bound to hydrophobic substrate materials, such as textiles, is characterized by a uniform or substantially uniform positive charge density across the surface area of the material. In some embodiments, the space charge electret material has a positive charge density of 9.59 nC cm -2 The disinfecting effect increases with increasing positive charge density. Figures 9-11 and 13 show that the space charge electret material with both high positive charge density and suitable hydrophobicity is found to have excellent antibacterial, antiviral, bactericidal and virucidal effects against Staphylococcus aureus, SARS-229E, SARS-CoV-2 and Coxsackievirus B6 with efficacy of over 98% in 5 minutes.
[0114] Use of Space Charge Electret Materials Space charge electret materials can be applied and used in many ways in antibacterial, antiviral, bactericidal and virucidal applications. Figure 3 illustrates the surface modification of a textile substrate with a space charge electret material of high positive charge density to obtain an antiviral and antibacterial textile. In a preferred embodiment, the surface modification of a textile substrate with a space charge electret material produces a uniform or substantially uniform (equal, constant, or substantially equal and / or constant) high positive charge density across the surface of the material. The material of the textile substrate can be natural cotton, wool, cellulose, synthetic polyester, nylon and blends thereof. The structure of the textile substrate can be knitted, woven and non-woven. A blended textile substrate refers to a textile substrate woven or knitted with two or more different textile substrates. Their hydrophobicity or amphiphilicity can be adjusted by blending. The textile substrate contains both hydrophilic and hydrophobic fiber regions, but together they show an overall hydrophobic or hydrophilic performance. In other words, the blended textile substrate contains both hydrophilic and hydrophobic fibers. When blending more hydrophobic fibers than hydrophilic fibers, the final surface wettability of the 2D knitted / woven textile substrate is hydrophobic. The influence of the fabric structure also plays a major role, such as 3D spatial fabrics. These surface wettability mainly depends on the surface layer. If the surface layer is knitted with 100% hydrophilic fibers, they are hydrophilic. These surface wettability can also be adjusted by controlling the fiber composition of the surface layer of the 2D fabric, etc. Based on the material and structure of the textile substrate used, the space charge electret material with antibacterial, antiviral, bactericidal and virucidal effects can be used for novel self-disinfecting filter products, such as masks, protective clothing and air purifiers, which can maintain high air permeability and particle / bacteria / virus filtration effectiveness. They can also be used in personal and household cleaning and sanitary products, such as hand sanitizers, wet tissues and toilet paper, household / hotel textile products, and related disposable products.
[0115] With reference to FIG. 4, the use of space charge electret materials for high-efficiency air filters with unique self-disinfecting function is illustrated and demonstrated. The fibers of textile treated with amphiphilic space charge electret materials are three-dimensionally conformed and positively charged. When biological hazardous substances (e.g., bacteria and viruses) pass through the textile, the fiber network plays a blocking role, and the highly positively charged fiber surface captures the biological hazardous substances with negative charge through non-contact electrostatic interaction / attraction. This strong electrostatic field makes the biological hazardous substances collide with the fiber surface, generating a surge of electric stress through contact charging to pin them firmly to the positively charged fiber surface. Finally, the biological hazardous substances are destroyed by rupture / shear of the protein envelope and / or other major viral or microbial proteins of the biological hazardous substances based on the combined effect of non-contact electrostatic interaction, contact charging and van der Waals force interaction. Thus, an air filter with unique self-disinfecting function can be developed by selecting a suitable textile substrate to load with space charge electret materials. These air filters of the present invention can capture bacteria and viruses and prevent them from passing through the filter and entering the filtered air, thereby killing the bacteria and viruses and preventing contact infection.
[0116] Methods of Making Antimicrobial Compositions Referring to FIG. 5, a flow chart of surface modification of a textile substrate material with a space charge electret material is illustrated based on using branched polyethyleneimine (BPEI) as a single component space charge electret. First, the BPEI space charge electret is dissolved in a suitable solvent to a desired concentration. Suitable solvents for BPEI include, but are not limited to, water, alcohol (e.g., ethanol), and mixtures thereof. BPEI can be dissolved in a suitable solvent, such as water or ethanol, at any concentration. By way of example, a suitable solvent can be at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95% or 100% ethanol (or water). In other words, a suitable solvent can be 95% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less ethanol (or water). Combinations of any of these are possible in some cases, for example, a suitable solvent may be 10-20%, 30-70% or 50-95% ethanol. In some embodiments, a suitable solvent is water, including up to 100% water. In some embodiments, the BPEI concentration for surface modification of the textile substrate material ranges from 1% to 10%. By way of example, the BPEI concentration may be about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9% or about 10%. By way of further example, the BPEI concentration may be at least 1%, at least 2%, at least 3%, at least 4%, at least 5%, at least 6%, at least 7%, at least 8% or at least 9%. In other words, the BPEI concentration may be 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less or 2% or less. Combinations of any of these are also possible in selected preferred embodiments, for example the BPEI concentration may be 1-2%, 3-7% or 5-9%.In other selected embodiments, linear polyethyleneimine is used as the space charge electret material, correspondingly comprising concentrations that correlate respectively with the concentrations of BPEI in the preferred embodiments.
[0117] Secondly, BPEI is introduced into the desired textile substrate material by either dip coating or spraying. The preferred textile substrate material involves cellulose and cellulose / polyester nonwoven fabric. Thirdly, the solvent needs to be removed from the textile substrate loaded with BPEI solution, which can be carried out by air drying or by drying at high temperature for faster solvent evaporation. Preferably, the drying temperature does not exceed 100°C. Finally, the textile substrate material modified with BPEI space charge electret (BPEI modified textile) can be used for systematic testing and evaluation, such as contact charging performance evaluation, antiviral test, antibacterial test, viral filtration test and bacterial filtration test.
[0118] Method for evaluating contact electrification performance FIG. 6 illustrates a schematic of a charge measurement device for evaluating the contact charging performance of space charge electret materials, as well as a typical charge curve resulting from controlled repeated contact and separation with repeated application and release of an external force. Specifically, the method for measuring the positive charge of space charge electret materials is based on a double-layer device that is mainly composed of a lower acrylic plate on which an adhesive electrode layer is fixed and an upper acrylic plate on which a reference material / electrode layer of the same size is fixed. In some embodiments, the adhesive electrode layer (and therefore the reference material / electrode layer of the same size) is 6 cm x 6 cm. In other embodiments, adhesive electrode layers with other dimensions and surface sizes are used. In some embodiments, a PTFE film is fixed as the reference material. As an example, other materials, such as polydimethylsiloxane (PDMS), can be fixed as the reference material. Different reference materials give different measurement (reference) values. PTFE has a high electronegativity and is particularly useful as a reference material for measuring the positive charge performance of other test samples. The test samples can be woven / knitted / non-woven samples and films. The material of the textile / fabric substrate can be natural cotton, wool, cellulose, synthetic polyester, nylon and / or blends thereof. The structure of the textile / fabric substrate can be knitted, woven and non-woven. When testing, the sample (e.g., the non-woven textile substrate surface modified with space charge electret material) is smoothly and firmly attached to the adhesive electrode of the lower acrylic plate. The upper acrylic plate can be mechanically controlled to repeatedly contact / impact the lower acrylic plate. This allows the surface of the space charge electret material modified textile to contact the PTFE surface by external pressure, and can be separated by releasing the external pressure. An electrometer is connected to the electrode for real-time monitoring and measurement of the charge fluctuation. The stable charge curves measured by repeated contact and separation were recorded for further analysis. In general, the maximum charge value appears at the contact state, while the minimum charge value is shown at the separation state. The value difference between the contact state and the separation state can be considered as the positive charge generated by contact electrification. The positive charge density is calculated using the positive charge divided by the effective contact area (e.g., 6 cm x 6 cm) and can be used for a quantitative assessment of the degree of contact electrification.In other words, the charge density (σ) can be calculated by σ=Q / S, where Q is the total charge and S is the surface area.
[0119] Space charge electret material concentration and charge density of textile substrate FIG. 7 shows the effect of single component space charge electret material (e.g., BPEI) concentration on the charge density of the textile substrate. A 40 g sample of spunlace (50% cotton / 50% polyester) was used as the textile substrate for the introduction of a given amount of space charge electret material. The aqueous solution concentration of BPEI space charge electret for surface modification of textile substrates ranged from 0 to 30 wt%. Referring to FIG. 7, the C-polar (e.g., BPEI) concentration was varied from 0% wt to 8 wt%, and the charge density increased proportionally due to constructive interference at the spunlace surface. However, when the C-polar concentration was 8 wt% to 30 wt%, the charge density dropped significantly because the overloaded C-polar destroyed the texture and microstructure of the spunlace and destroyed the constructive interference on the polarity.
[0120] Different single component space charge electret materials have different positive charge density values. Some examples are shown in Table 1.
[0121] [Table 5]
[0122] Thus, the positive charge density of the textile substrate can be adjusted by adjusting the solution concentration and components of the space charge electret material.
[0123] To obtain a modified textile with a high positive charge density, a single component space charge electret material with a high charge density and suitable concentration can be selected. To obtain a modified textile with a suitable positive charge density and hydrophobicity, a multi-component space charge electret material can be selected based on different types of cationic polymers and components. The selection of a cationic polymer with high hydrophobicity can use a polymer with a low density of cationic groups and a long alkyl chain. In selected preferred embodiments of the present invention, the high positive charge density of the modified textile is applied and obtained uniformly or substantially uniformly over the entire surface area of the textile.
[0124] Figure 8 shows the instantaneous output voltage generated when a textile surface modified with a high positive charge density space charge electret material was repeatedly contacted / impacted. The results demonstrate the sudden change in electrostatic potential upon contact electrification.
[0125] Antiviral Effectiveness Referring to FIG. 9, the antiviral activity test against SARS-CoV-2 of the textile substrate (i.e., BPEI spunlace) treated with the space charge electret material was performed according to ISO 18184. First, 50 μl of SARS-CoV-2 (100,000 PFU / ml) was applied to a 1×1 cm spunlace treated with the space charge electret material. 2The test textile substrate material and the control were added in triplicate. The test textile substrate was covered with glass and incubated at room temperature for 5 or 30 minutes. After incubation, the test textile substrate was transferred to 5 ml of DMEM complete medium, vortexed 5 times for 5 seconds, 200 μl of medium was transferred to VERO-E6 cells, and the residual virus titer was determined by plaque assay. The virus in the cells (250,000 cells / well) in a 24-well plate was mixed gently and incubated at 37°C in a CO2 incubator for 4 hours. Then, 0.4 ml of 3% carboxymethylcellulose was added and then incubated for 5 days. After incubation, the cells were washed, stained with naphthol blue black dye, rinsed with water, dried, and the plaques were counted. The titer was expressed in pfu / ml and the virus yield reduction was expressed as a percentage, as shown in Figure 9. The virucidal performance of different textile substrates (e.g., cellulose and cellulose / polyester substrates) treated with different solution concentrations of C-Polar (BPEI) (i.e., 4%, 6% or 8% BPEI space charge electret material) was summarized. Briefly, cellulose / polyester textiles treated with BPEI showed better overall virucidal efficacy than cellulose textiles treated with BPEI. Cellulose / polyester textiles treated with 6% BPEI space charge electret material eliminated 98% of SARS-CoV-2 after 5 minutes of exposure and 99.6% of SARS-CoV-2 after 30 minutes of exposure, respectively. 100% viral elimination was achieved in one of the biological replicate studies. The reason for this can be attributed to the synergistic effect of the high positive charge density and favorable oleophilicity (i.e., hydrophobicity) of the BPEI modified fabric. Due to the hydrophobic component of polyester, cellulose / polyester blend textiles generally exhibit higher hydrophobicity than single component cellulose textiles. As described above, the hydrophobicity of amphiphilic materials also plays an important role in the insertion of lipophilic segments into the membrane via van der Waals interactions. This lipophilic property contributes to enhancing the electric stress generated by the strong electrostatic field to cleave the envelope proteins of biohazardous materials and / or other major viral or microbial proteins of biohazardous materials (see FIG. 1 and paragraph
[0085] ).A suitable increase in BPEI can significantly increase the positive charge density, but can also increase the hydrophilicity of the textile substrate. Excessive increase in BPEI can result in embedding of the hydrophobic surface of the textile and a decrease in the lipophilicity, thereby slightly decreasing the virucidal efficacy.
[0126] 10 and 11, antiviral activity tests were carried out on textile substrates (e.g., 4% BPEI spunlace or 4% C-POLAR spunlace) treated with space charge electret materials against human coronavirus 229E and Coxsackievirus B6. First, 2.5×2.5 cm test pieces of the test textile material were immersed in 200 μl of buffer solution containing virus (50000 PFU) and incubated at room temperature for 5 minutes or 60 minutes, respectively. Then, the tubes containing the test textile material and buffer solution were centrifuged. After the test textile material was removed from the buffer solution, the virus concentration in the buffer solution was tested using RT-qPCR. The test results of different textile materials that kill human coronavirus 229E and Coxsackievirus B6 were shown. The textile materials used included tissue (100% cellulose), FFP2 filter (nonwoven polyester), FFP2 sponge (nonwoven), Curie spunlace (i.e., cellulose / polyester textile treated with 4% BPEI space charge electret material) and Curie paper (i.e., cellulose treated with 4% BPEI space charge electret material). Both cellulose textile and cellulose / polyester treated with BPEI showed surprisingly better virucidal performance than textiles without BPEI space charge electret material (e.g., tissue, FFP2 filter and FFP2 sponge). Most surprisingly, the results demonstrated that the textile substrate treated with BPEI was 10,000 times more effective than conventional filtration media for antiviral activity. In addition, the fact that similar effects were obtained from two viruses with different structural aspects (enterovirus and coronavirus) demonstrates that the BPEI space charge electret material on both polyester / cellulose textile substrate and cellulose textile substrate works well for eliminating different types of viruses. These two viruses represent an enveloped virus (coronaviruses with a lipid bilayer structure) and a non-enveloped virus (enteroviruses with a capsid structure), which means that their surface structures are very different.In addition, the observed 99.9% reduction of virus in buffer was already seen after the shortest incubation time tested (5 min), suggesting a rapid effect of the polyester / cotton and cellulose materials against the virus, a core feature important for the functionality of the mask materials, suggesting high efficacy in sequestering the virus.
[0127] Referring to FIG. 12, the viral filtration effectiveness test was adapted from ASTM F2101, US FDA Good Manufacturing Practice (GMP) regulations 21 CFR Parts 210, 211 and 820. The viral filtration efficiency (VFE) of the test article was determined by comparing the virus control counts upstream of the space-charged electret material-treated textile substrate (e.g., C-POLAR spunlace with 2%-9% BPEI spunlace or nonwoven fibers) to the downstream counts. Five test articles were tested at Nelson Labs and another five test articles were tested at Intertek's laboratory. Briefly, a suspension of bacteriophage φX174 was aerosolized using a nebulizer and delivered to the space-charged electret material-treated textile substrate material at a constant flow rate and fixed air pressure. The load delivery sustained 1100-3300 plaque-forming units (PFU) at a mean particle size (MPS) of 3.0±0.3 μm. The test area is approximately 40 cm 2 The VFE flow rate was 28.3 liters per minute (L / min) at 85 ± 5% relative humidity and 21 ± 5°C for a minimum duration of 4 hours. The positive control average was 1.6 × 10 3 PFU and the negative monitor count was <1 PFU. Aerosol droplets were drawn by a 6-stage bioparticle Anderson collection sampler. Results showed that the woven substrates treated with space charge electret material were effective in preventing viruses from penetrating through the woven filters. Cellulose / polyester fabrics treated with BPEI space charge electret material demonstrated a viral filtration efficacy of >99.9%. No plaques were detected on any of the Andersen sampler plates.
[0128] Antibacterial Effectiveness 13 and 14, antibacterial activity tests were conducted on textile substrates (2% to 9% BPEI spunlace) treated with space charge electret materials. Briefly, textile substrates treated with space charge electret materials were washed 60 times in a washing machine with cold water and detergent. 6 CFU / ml ~3×10 6 A 1 milliliter inoculum of S. aureus at a concentration of CFU / ml was applied to the agar plate by the transfer method, and each textile substrate treated with space charge electret material was placed on the agar surface and pressed down with a 200 g stainless steel cylinder for 60 seconds ± 5 seconds to transfer the microbial content. Measurement of bacterial colony counts was performed according to the plate count method specified in Annex C of BS EN ISO 20743:2013. The test results of different textile substrates treated with BPEI space charge electret material for the killing of S. aureus without washing, before washing and after 60 washings were summarized. According to the method of Wiegand C., Heinze T. and Hipler UC (2009), Comparative in vitro study on cytotoxicity, antimicrobial activity, and binding capacity for pathophysiological factors in chronic wounds of alginate and silver-containing alginate. Wound Repair Regen., 17, 511-521, antimicrobial activity values below 0.5 are determined to represent no antimicrobial activity. Values of 0.5-1 are ranked as mild activity, values above 1 to 3 are ranked as significant activity, and a log reduction of more than 3 represents strong antimicrobial activity.
[0129] [Table 6]
[0130] [Table 7]
[0131] Taken together, the results show that both the 50% cotton / 50% polyester fabric and the 35% cellulose / 65% polyester fabric treated with the BPEI space charge electret material killed S. aureus with greater than 99.9% efficacy. The antibacterial activity values of the fabric substrates after 60 washes were greater than 3, indicating that 60 washes have little effect on the strong antibacterial activity of the BPEI-treated cellulose / polyester fabric materials.
[0132] Referring to FIG. 15, the effectiveness of the space charge electret material treated filter in stopping bacteria from penetrating through the filter by high velocity airflow was evaluated. The bacterial filtration efficiency test was adapted from ASTM F2101:2019. The bacterial filtration efficiency (BFF) of the test article was determined by comparing the bacterial control count upstream of the space charge electret material treated textile substrate (2%-9% BPEI spunlace with 50% cotton / 50% polyester) with the count downstream. Briefly, a suspension of Staphylococcus aureus in peptone water was aerosolized using a nebulizer and delivered to the space charge electret material treated textile substrate with a constant flow rate, fixed air pressure of 21±5°C and relative humidity of 65±5% for a minimum time of 4 hours. The load delivery sustained 2200 colony forming units (CFU) at a mean particle size (MPS) of 3.0±0.3 μm. Aerosol droplets were drawn through tryptic soy agar plates by vacuum collection (flow rate: 100 liters per minute). After 48±4 hours of incubation at 37±2°C, the number of Staphylococcus aureus colonies formed on the tryptic soy agar plates was counted. The results showed that the 50% cotton / 50% polyester fabric treated with BPEI space charge electret material achieved a bacterial filtration effectiveness of over 99.9%. No detectable bacterial colonies of Staphylococcus aureus were found. These results demonstrate that the cotton / polyester fabric treated with BPEI space charge electret material stopped all penetrating bacteria penetrating the filter when high velocity airflow was used.
[0133] Bacterial toxicity 16 and 17, the effect of cellulose and cellulose / polyester fabrics treated with different solution concentrations of BPEI space charge electret material on the viability of VERO E6 cells was investigated, respectively. Briefly, 1×1 cm woven fabrics treated with 4%, 6% or 8% BPEI space charge electret material were used. 2 Woven fabric substrates (C-POLAR) were incubated in 10 ml of DMEM complete medium for 30 min. After incubation, the medium was transferred in triplicate at 10-fold dilutions to VERO E6 cells in 96-well plates and incubated at 37 °C, 5% CO2 for 72 h. Cell viability was determined by adding XTT solution for 4 h and the absorbance of the newly formed orange formazan solution was measured using an En Vision plate reader. Absorbance was normalized to the no sample control, which was set at 100%, and log-Seq was calculated by GraphPad software. 10 Plotted against dilution. The results show that washout from control and space charge electret material treated fabrics moderately reduced VERO E6 cell proliferation. There was no difference in VERO E6 cell proliferation between untreated and C-polar treated fabrics over 3 days of incubation.
[0134] Referring to FIG. 18, the cytotoxicity of different concentrations of BPEI space charge electret material (C-POLAR) against GMK (green monkey kidney) cells and MRC5 (Medical Research Council cell line 5 derived from human lung tissue) cells was investigated. Using cell culture medium, liquid formulations of BPEI space charge electret material were diluted to 8%, 4%, 2%, 1%, 0.5%, 0.25%, 0.124%, etc. The diluted BPEI space charge electret material was transferred to a culture plate, and then an equal volume of cell suspension in complete medium was added to each well, replicated in eight parallel wells in a 96-well plate. The cells were incubated at 37° C. for 5 days until the plate bottom of each well was covered with cells. The cells were fixed and stained at the end of the 5th day to visualize the viable and replicating cells. The results demonstrated that 0.5% of the BPEI space charge electret material remained equivalent to the control over the 5-day incubation. It was also demonstrated that when 8.3% of the total polymer of the textile substrate treated with the BPEI space charge electret material was abraded, no significant cytotoxicity occurred against GMK and MRC5 cells.
[0135] 19 and 20, the effect on cell sensitivity of woven cellulose and cellulose / polyester fabrics treated with different solution concentrations of BPEI space charge electret material was investigated. Briefly, 1×1 cm woven fabrics treated with 4%, 6% or 8% BPEI space charge electret material were used. 2The textile substrates were washed with 10 ml of DMEM complete medium by vortexing five times for 5 seconds. 5 ml of medium was transferred to another tube, 50 μl of SARS-CoV-2 (100,000 IU / mL) was added, and the mixture was incubated at room temperature for 30 min. After incubation, 200 μl of the mixture was removed and titrated by plaque assay in 24-well plates in DMEM complete medium using 10-fold dilutions. The virus on the cells (250 000 / well) was mixed gently and incubated at 37 °C for 4 h. After that, 0.4 ml of 3% carboxymethylcellulose was added, and the plates were then incubated for 5 days. After incubation, the cells were washed, stained with naphthol blue-black dye, washed with water, and dried. The plaques were counted in pfu / ml and calculated as log 10 and log 10 Log of virus titer compared to pfu / ml 10 The difference was determined. The results showed that no reduction in cell sensitivity was found.
[0136] 21A-21C, the ISO 10993-5 test (test for in vitro cytotoxicity), the ISO 10993-10 test (animal skin irritation test) and the ISO 10993-10 test (skin sensitization test) were performed on textile substrates treated with 2%-9% BPEI space charge electret material to determine the biocompatibility of the treated textile substrates. For the in vitro cytotoxicity test, the treated textile substrates were sterilized at 121° C. for 30 minutes and irrigated with 1640 medium at 3 cm. 2 The cells were extracted at a ratio of 0.1% zinc diethyldithiocarbamate (ZDEC) / ml for 24 hours at 37°C. The positive control was a polyurethane film containing 0.1% zinc diethyldithiocarbamate (ZDEC). Mouse fibroblast L929 cells were cultured in RPMI 1640 medium supplemented with L-glutamine, 10% FBS, and penicillin-streptomycin at 37°C and 5.0% CO2. L929 cells were seeded in a 96-well plate, and 100 μl of cell solution was added to each well at a concentration of 1 × 10 5The cells were added at a density of 1000 cells / ml. L929 cells were treated with the extraction medium of the treated textile substrate, and six replicate wells were used. After 24 hours of treatment, 50 μl of MTT solution was added to each well. After incubation, washing and isopropanol extraction, the absorbance of each well was detected at 570 nm by a spectrophotometer, and the cell viability was calculated. The results in FIG. 21A showed that the cytotoxicity of the textile substrate treated with BPEI space charge electret material was grade 0, which was considered to be non-cytotoxic.
[0137] Four healthy normal female New Zealand white rabbits, each weighing 2.0-3.0 kg, were used in the animal skin irritation test. The rabbits were kept at room temperature (18-23 °C) with a relative humidity of 45-65%. The results in Figure 21B showed that the textile substrates treated with 2%-9% BPEI space charge electret material were found to be negligible irritant to rabbit skin according to the rabbit primary irritation index classification.
[0138] In the skin sensitization test, female guinea pigs, each weighing 300-500 g, were used. The guinea pigs were kept at room temperature (20-22 °C) with a relative humidity of 45-65%. The results in Figure 21C showed that the textile substrates treated with the BPEI space charge electret material did not cause delayed-type skin contact sensitization in the guinea pigs. In summary, it is clear that the textile substrates treated with the BPEI space charge electret material are biocompatible materials.
[0139] Method for loading space charge electret material onto textile substrate Referring to FIG. 22, a method of loading space charge electret material onto the surface of a textile substrate is shown. The textile substrate is formed into a dry web by carding. In an exemplary embodiment, the textile substrate can be natural cotton, wool, cellulose, synthetic polyester, nylon and / or blends thereof. The space charge electret material is loaded onto the fabric surface of the dry web by a high pressure liquid stream to form a nonwoven fabric. A special in-line process is performed. The space charge electret material is then cross-linked with the fabric surface by drying and winding under high temperature to form the surface of the textile substrate.
[0140] Referring to FIG. 23, a flow chart is presented for the design and fabrication of biocompatible space charge electret materials with high charge density based on cationic polymers and textile substrates for antibacterial, antiviral, bactericidal and virucidal applications. One or more cationic polymers with different positive charge density and surface wettability (hydrophilic and / or hydrophobic) can be selected for the design and fabrication of high charge density space charge electret materials with suitable hydrophobicity to meet the specific requirements of the target application. The hydrophilicity of the space charge electret materials can be adjusted by the type and density of cationic carrying groups, while the hydrophobicity can be adjusted by the length of the hydrophobic alkyl chain and the hydrophobic group. These can be dissolved in a suitable solvent for the preparation of homogeneous dispersions and modified on textile substrates by a combination of dip coating / spraying and drying. To achieve good antibacterial, antiviral, bactericidal and virucidal effects, the positive charge density of the space charge electret materials should be at least 9.59 nC cm -2 In a preferred embodiment, the positive charge density of the space charge electret material is uniform or substantially uniform (constant) across the surface area of the electret material. In some embodiments, the woven substrate is composed of hydrophobic fibers. To achieve biocompatible performance, the composition (e.g., components and component ratios) is controlled to be non-toxic.
[0141] Methods for preparing binding compositions 24A-24B illustrate a method of preparing a linker composition of the present disclosure, in which linear or branched PEI is hydrogen bonded to a fiber substrate (an example of a hydrophobic material). Such hydrogen bonding is achieved by first dissolving a certain amount of linear or branched PEI in water at 20° C. to form a 6 wt % solution of PEI in water. This is followed by dip-coating the fiber substrate into the resulting PEI solution and / or spraying the resulting solution onto the fiber substrate. In some preferred embodiments, the fiber substrate is immersed in the PEI solution for 2-10 seconds. Finally, the immersed fiber substrate is optionally air-dried with heat, preferably 50° C.-160° C., for at least 5 seconds, and / or optionally subjected to a tension forming process, which may include one or more of the following actions: stretching, steaming, heating, applying pressure, and / or applying pressure to the coated fiber substrate, including high pressure air flow or mechanical pressure. The resulting PEI coated fibrous substrates are validated by measuring the variation in basis weight (grams per square meter), where a limited variation tolerance is considered acceptable.
[0142] In the most preferred embodiment of the present invention, a tension forming process is applied to the subject coated fibrous substrate material, where "tension forming process" includes one or more of the following actions: stretching, steaming, heating, applying pressure, or applying pressure to the material, including high pressure air flow or mechanical pressure. For example, the fibrous substrate material can be drawn into a heated chamber by rollers and dried at an elevated temperature, for example, 160°C. It is understood that the application of force to the woven substrate material can be adjusted by the rollers. Furthermore, the drying time and temperature can also be adjusted. In some exemplary embodiments, the temperature is 100°C to 200°C, 150°C to 200°C, 150°C to 175°C, 175°C to 200°C, 150°C to 170°C, or 155°C to 165°C. In the most preferred embodiment, the temperature is 160°C.
[0143] The resulting PEI coated fibrous substrate material was validated by measuring the variation in basis weight (grams per square meter), where a variation of 10% is considered acceptable.
[0144] The mass variation of the PEI modified woven fabric can be calculated by W=(m1-m0 / m0)×100%, where m1 is the basis weight of the PEI modified woven fabric substrate material and m0 is the basis weight of the pristine woven fabric substrate material.
[0145] Branched PEI: Selected Exemplary Embodiment 1 In an exemplary embodiment, 60 g of branched PEI polymer (MW 20000) is dissolved in 940 ml of water at room temperature and stirred for at least 5 minutes to form a 6% branched PEI solution. A 0.30 mm thick 50% polyester / 50% cotton cellulose textile material is immersed in the 6% branched PEI solution for 2-10 seconds or sprayed onto the textile material by a shower spray in a shower chamber. Once thoroughly wetted, the textile material undergoes a tension forming process, where the PEI coated textile is pulled into a heating chamber by rollers and dried at 160°C for at least 5-20 seconds. "Tension forming" may also include one or more of the following actions: stretching, steaming, heating, applying pressure, and / or applying pressure to the material, including high pressure air flow or mechanical pressure. The resulting coated textile material is characterized by basis weight measurements and FT-IR attenuated total reflectance (ATR) spectroscopy. The antimicrobial properties may be confirmed by the tests described herein.
[0146] Branched PEI: Selected Exemplary Embodiments II In another exemplary embodiment, 40 g of branched PEI polymer (MW 25000) is dissolved in 960 ml of water at room temperature and stirred for at least 5 minutes to form a 6% branched PEI solution. A 0.30 mm thick 50% polyester / 50% cotton cellulose textile material is immersed in the 6% branched PEI solution and then dried at 160° C. for 10 seconds. The resulting coated textile material is characterized by basis weight measurement and FT-IR attenuated total reflectance (ATR) spectroscopy.
[0147] Pristine 50% polyester / 50% cotton cellulose fabric with a basis weight of 35-75g / m 2 A 50% BPEI modified polyester / 50% cotton cellulose textile material treated with 1% to 6% BPEI solution according to the examples disclosed above has a mass variation W of 10% to 70%.
[0148] Linear PEI: Selected Exemplary Embodiments In another preferred embodiment, 500 mg of linear PEI polymer is dissolved in 500 ml of water to form a homogeneous and transparent solution. A 0.30 mm thick 50% polyester / 50% cotton cellulose textile material is used as the substrate, which is immersed in the linear PEI solution for 5 minutes, then removed and air-dried. In most preferred embodiments, when the wet substrate no longer drips liquid under gravity conditions, it is transferred to a 60°C oven for accelerated drying. Both sides of the dry substrate are ironed at 160°C. Finally, it is dried at 60°C to obtain a linear PEI modified 50% polyester / 50% cotton cellulose textile material. The resulting coated fabric is characterized by basis weight measurement and FT-IR attenuated total reflectance (ATR) spectroscopy.
[0149] The antimicrobial properties of the PEI and BPEI modified fabrics can be confirmed by the tests described herein.
[0150] Method for preparing Si-linker composition Figures 25A-25B illustrate one method in which silyl linkers bearing epoxide groups are first attached to the fiber substrate (hydrophobic material) and to each other via a single -O-linker, and then combined with linear or branched PEI via an epoxide ring-opening reaction.
[0151] In an exemplary embodiment, 10 g of 3-glycidyloxypropyltrimethoxysilane (Figure 25A(i)) is dissolved in 1000 mL of acetic acid / water solution at room temperature. The pH of the aqueous solution is adjusted to 5.3 by adding acetic acid. The methoxy groups react with water by hydrolysis to form a 1% aqueous silane solution of the compound of Figure 25A(ii). A fiber substrate, for example a 0.30 mm thick 50% polyester / 50% cellulose material, is then immersed in the 1% aqueous silane solution. The solution is heated to 40°C and held for 2 hours, resulting in a compound of formula 25A(iii), in which at least some of the silyl linkers are bonded to each other via a single -O-linker. This reaction also results in the bonding of the compound of formula 25A(iii) to the fiber substrate via the -O-linker to form a compound of formula 25A(iv). The modified fiber substrate 25A(iv) is removed from the solution for "draining water in the air", meaning that a portion of the excess water is removed by physical means, such as draining in the air or gravity dripping. In most preferred embodiments, the modified fiber substrate 25A(iv) is then transferred to an oven and further heated and dried at 60° C. for 2 hours. After the water is completely removed (i.e., the modified fiber substrate 25A(iv) is completely dried), the dried modified fiber substrate 25A(iv) is further washed with pure water to remove any remaining starting materials, unreacted compounds, and acetic acid. The washed modified fiber substrate 25A(iv) is redried at 60° C. for 2 hours. After drying, the modified fiber substrate 25A(iv) is immersed in a linear PEI solution doped with lithium perchlorate and further tensioned at 160° C. for at least 10 seconds, such that the PEI polymer and linker are bonded via an epoxide ring-opening reaction to form a compound of formula 25A(v). The linear PEI modified fiber substrate of Formula 25(A)(v) is transferred to an oven and heated at 60° C. for 2 hours. Finally, the compound of Formula 25(A)(v) is washed with pure water to remove unreacted or unbound polymer and catalyst, and redried at 60° C. for 2 hours. Branched PEI is also chemically bound to the fiber substrate by the same procedure, as shown in FIG. 25B.
[0152] FIG. 26A illustrates the process steps for attaching the cationic polymer of the present disclosure to a textile / fiber substrate. First, a cationic polymer solution is prepared by dissolving one or more cationic polymers in a suitable solvent. The textile / fiber substrate is then coated with the cationic polymer solution by dripping, spraying, dip coating, or other methods known to those skilled in the art. In selected preferred embodiments, the substrate is coated with the cationic polymer in such a manner that the coating and resulting positive charge density is uniform or substantially uniform throughout the surface area of the textile / fiber substrate. The textile / fiber substrate coated with one or more cationic polymers is then subjected to tension formation. "Tension formation" includes one or more of the following: stretching, steaming, heating, pressurization, and application of pressure, including high pressure air flow or mechanical pressure, during and / or after which one or more cationic polymers are hydrolyzed and then dehydrated, where certain silyl-hydroxyl groups may optionally condense with each other. By way of example, cationic polymers with silyl linkers are attached to each other via a single -O-linker. The dehydrated / condensed cationic polymer then forms hydrogen bonds with the textile / fiber substrate, followed by chemical bonds between the dehydrated / condensed cationic polymer and the hydroxyl groups of the textile / fiber substrate. After tension formation, the mixture is washed to remove unbonded components and then dried to obtain the textile / fiber substrate with the cationic polymer.
[0153] FIG. 26B shows an exemplary schematic of how the branched cationic polymer is bonded to the fiber substrate. The branched cationic polymer 26B(i) with a silyl linker is dissolved in water under hydrolysis conditions to form a solution of the branched cationic polymer 26B(ii) with a silyl linker. The fiber substrate is then immersed in a 6% solution of the branched cationic polymer 26B(ii) with a silyl linker at 40° C. for 2 hours to form first the branched PEI linked fiber substrate 26B(iii) and then the antimicrobial composition of formula 26B(iv). The modified fiber substrate containing the mixture of the compounds of formula 26B(iii) and formula 26B(iv) is removed from the solution, drained in air, and then transferred to an oven and heated at 60° C. for 2 hours to form the compound of formula 26B(iv). After complete drying, the modified textile substrate of formula 26B(iv) is washed with pure water to remove excess or unreacted compounds and redried at 60° C. for 2 hours to obtain the antimicrobial composition of formula 26B(iv), a textile / textile substrate having a surface modification of branched PEI.
[0154] In an exemplary embodiment, 20 g of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane is dissolved in 1000 mL of aqueous solution at room temperature to form a 2% silane solution. A fiber substrate, such as a 0.30 mm thick 50% polyester / 50% cellulose material, is then immersed in the 2% silane aqueous solution. The solution is heated to 40° C. and held for 2 hours. During this immersion process, the methoxyl groups of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane react with water via hydrolysis to form silanol groups, which are chemically bonded to the fiber surface via a dehydration / condensation reaction with the hydroxyl groups of the fiber. 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane can also be first bulk polymerized into an oligomeric structure via a silanol self-condensation reaction, and then grafted to the fiber surface via an -O-linker. The modified textile substrate is removed from the solution, taken out, allowed to drain in air, and transferred to an oven for 2 hours at 60° C. After complete drying, it is washed with pure water to remove unbound compounds, and redried at 60° C. for 2 hours to obtain a textile / textile substrate with surface modification of linear PEI molecules and oligomers.
[0155] 27A-27B show exemplary synthetic routes to make various silylated linear or branched PEI compounds via silylation reactions between chloroalkoxysilanes and PEI polymers (exemplary cationic polymers).
[0156] In an exemplary embodiment, 500 mg of linear PEI polymer is dissolved in 200 mL of ethanol in a sealed container. The container is placed in an ice bath (0° C.) and nitrogen gas is bubbled through the solution to remove oxygen. 5 g of chlorotriethoxysilane is then slowly dripped into the solution over 30 minutes and stirred continuously at 0° C. for 1 hour under N2-filled environment, followed by stirring at 40° C. for 2 hours. The solution is then poured into an excess of diethyl ether to obtain a precipitate of silylated linear PEI polymer, which is collected by filtration and further dried under vacuum.
[0157] In another exemplary embodiment, 10 g of branched PEI polymer is dissolved in 500 mL of ethanol in a sealed container. The container is placed in an ice bath (0° C.) and nitrogen gas is bubbled through the solution to remove oxygen. 20 g of chlorotriethoxysilane is then slowly dripped into the solution over 30 minutes and stirred continuously at 0° C. for 1 hour under N2-filled environment, followed by stirring at 40° C. for 2 hours. 500 mL of diethyl ether is then poured into the solution, resulting in liquid stratification. A separate funnel is used to obtain the liquid layer containing the silylated branched PEI polymer. The final product is further dried under vacuum and in a sealed storage unit.
[0158] 27C-27D show an exemplary synthetic route for reacting silylated linear or branched PEI with a fiber substrate (hydrophobic material). In an exemplary embodiment, 100 mg of silylated linear PEI polymer is dissolved in 100 mL of ethanol / water (50 / 50, w / w) mixture at room temperature to form a Si-PEI solution. A fiber substrate, for example a 0.30 mm thick 50% polyester / 50% cellulose material, is then immersed in the Si-PEI solution at room temperature for 30 minutes, then heated to 40° C. and held for 2 hours. During this immersion process, the methoxyl groups of the silylated linear PEI polymer react with water via hydrolysis to form silanol groups. The silanol groups are chemically bonded to the fiber surface via a dehydration / condensation reaction with at least one hydroxyl group of the fiber substrate to form a modified fiber substrate. The modified fiber substrate is removed, drained in air, and transferred to an oven at 60° C. for 2 hours. After drying completely, it is washed with pure water to remove excess or unreacted compounds, and redried at 60° C. for 2 hours to obtain the textile / fiber substrate with surface modification of silylated linear PEI polymer (Formula 27C(iii)), which has chemical bonds between the silyl groups of the silylated linear PEI polymer and the hydroxyl groups of the fiber substrate.
[0159] In another exemplary embodiment, 6 g of silylated branched PEI polymer is dissolved in 100 mL of ethanol / water (50 / 50, w / w) mixture at room temperature. Then, a fiber substrate, for example, a 0.30 mm thick material of 50% polyester / 50% cellulose, is immersed in the as-prepared solution for 30 minutes. The solution temperature is further increased to 40° C. and held for 2 hours. During this immersion process, the methoxyl groups react with water via hydrolysis to form silanol groups, which chemically bond with the fiber surface via a dehydration / condensation reaction with the hydroxyl groups of the fiber. The modified fiber substrate is removed, drained in air, and transferred to an oven at 60° C. for 2 hours. After complete drying, it is washed with pure water to remove unbound compounds, and re-dried at 60° C. for 2 hours to obtain a textile / fiber substrate with surface modification of silylated branched PEI polymer (Formula 27D(iii)), which has chemical bonds between the silyl groups of the silylated branched PEI polymer and the hydroxyl groups of the fiber substrate.
[0160] Methods for designing and producing new antimicrobial compositions Provided herein is a new disinfection mechanism of space charge electret materials that capture and kill microorganisms (e.g., bacteria and viruses) through the synergistic effects of contact charging, non-contact electrostatic interaction and interfacial lipophilicity, which leads to the design and fabrication of biocompatible space charge electret materials with excellent antibacterial, antiviral, bactericidal and virucidal effects based on biocompatible cationic polymers and textile substrates. The space charge electret materials have both high positive charge density and suitable hydrophobicity to achieve excellent antibacterial, antiviral, bactericidal and virucidal effects. It is demonstrated that the positive charge density plays a major role in the degree of antibacterial and antiviral activity of space charge electret materials.
[0161] First, the space charge electret material with high positive charge density attracts the biohazardous substances (e.g., bacteria and viruses) with negatively charged proteins through non-contact electrostatic interactions, resulting in an increase in collision frequency. Then, contact charging occurs when the floating negatively charged biohazardous substances collide with the positively charged electret, resulting in a sudden change in electrostatic potential and a sudden increase in electric stress. The strong electrostatic field firmly pins or captures the biohazardous substances to the positively charged surface, and the generated non-uniform electric stress contributes to the shearing or rupture of the envelope proteins of the biohazardous substances and / or other major viral or microbial proteins. During close contact, the hydrophobicity of the space charge electret material helps the insertion of the lipophilic compartment into the membrane of the biohazardous substances via van der Waals interactions, contributing to easier and more rapid destruction of the biohazardous substances. By appropriate selection of the textile substrate with suitable structure, the space charge electret material based on the cationic polymer and textile substrate can have high virus and bacteria filtration effectiveness. Such types of space charge electret materials can be used extensively for air filtration products (e.g., masks, protective clothing, air filters and air purifiers), and personal / household cleaning and sanitary products, such as hand sanitizers, wet wipes and toilet paper, household / hotel textile products, and related disposable sanitary products.
[0162] Specific Exemplary Embodiment - Setting 1 Provided herein is a novel disinfection mechanism of space charge electret materials that capture and kill microorganisms (e.g., bacteria and viruses) through the synergistic effects of contact charging, non-contact electrostatic interaction and interfacial lipophilicity, leading to the design and fabrication of biocompatible space charge electret materials that feature excellent antibacterial, antiviral, bactericidal and virucidal effects based on biocompatible cationic polymers and textile substrates.
[0163] It is demonstrated that the positive charge density plays a major role in the degree of antibacterial and antiviral activity of space charge electret materials.
[0164] First, space-charged electret materials with high positive charge density attract target biohazardous agents (e.g., bacteria and viruses) with negatively charged proteins through non-contact electrostatic interactions, resulting in an increased collision frequency.
[0165] Contact charging then occurs when a floating negatively charged biohazardous material collides with a positively charged electret, resulting in a sudden change in electrostatic potential and a sudden surge in electrical stress. The strong electrostatic field anchors the biohazardous material tightly to the positively charged surface, and the generated non-uniform electrical stress contributes to the rupture or shearing of the envelope proteins and / or other key viral or microbial proteins of the target biohazardous material.
[0166] During close contact, the hydrophobicity of the space-charged electret material aids the insertion of the lipophilic compartment into the membrane of the biohazardous material via van der Waals interactions, contributing to easier and more rapid destruction of the biohazardous material.
[0167] Provided herein is a technological route using one or more cationic polymers and a hydrophilic fiber / hydrophobic blended textile substrate for the preparation of space charged electret materials with high charge density and suitable surface hydrophobicity.
[0168] Provided herein is a new application of using space charge electret materials for biocompatible disinfectants / sanitizers with excellent antibacterial, antiviral, bactericidal and virucidal effects.
[0169] Provided herein is a new application using space charge electret materials for air filters with high viral and bacterial filtration effectiveness.
[0170] To achieve excellent antibacterial, antiviral, bactericidal and virucidal effects, as well as high virus / bacterial filtration efficiency, the positive charge density of the textile substrate treated with cationic polymers was 9.59 nC cm -2 In some embodiments, the textile substrate is composed of hydrophilic fibers (e.g., cellulose) and hydrophobic fibers (e.g., polyester).
[0171] Provided herein are methods and devices for evaluating contact charging of space charge electret materials.
[0172] Provided herein is a parameter of positive charge density to quantitatively assess the degree of contact electrification.
[0173] Provided herein is a device for measuring the positive charge of space charge electret materials, which is based on a double-layer device mainly composed of a lower acrylic plate on which a 6 cm x 6 cm adhesive electrode layer is fixed, and an upper acrylic plate on which a reference material / electrode layer of the same size is fixed. A PTFE film is fixed as the reference material. The test sample can be a woven / knitted / non-woven sample and a film.
[0174] When testing, the sample (e.g., a non-woven textile substrate surface modified with space charge electret material) is smoothly and firmly attached to the adhesive electrode of the lower acrylic plate. The upper acrylic plate can be mechanically controlled to repeatedly touch / impact the lower acrylic plate. This allows the space charge electret surface to come into contact with the material modified textile (modified with PTFE) surface by external pressure, and can be separated by releasing the external pressure.
[0175] An electrometer is connected to the electrodes for real-time monitoring and measurement of charge fluctuations, and stable charge curves generated and measured by repeated contact and separation are recorded for further analysis.
[0176] Generally, the maximum charge value appears in the contact state, while the minimum charge value is exhibited in the separation state. The difference between the values in the contact state and the separation state can be determined as the positive charge generated by contact electrification. The positive charge density is calculated using the positive charge divided by the effective contact area (e.g., 6 cm x 6 cm) for a quantitative evaluation of the degree of contact electrification.
[0177] While various embodiments of the invention have been described, it will be apparent to those of ordinary skill in the art that many more embodiments and practices are possible and are within the scope of the invention. In addition, the various features, elements, and embodiments described herein can be claimed or combined in any combination or arrangement.
Claims
1. 1. An antiviral material comprising a cationic polymeric space charge electret material having antiviral properties bound to a hydrophobic substrate material, the cationic polymer being natural, semi-synthetic or synthetic; Further, the cationic polymer has a linear, branched, hyperbranched or dendritic structure, the cationic polymer comprising at least a cationic carrying group disposed on the backbone or side chains of the cationic polymer; The hydrophobic material has a surface that is positively charged in a uniform manner; Antiviral materials.
2. 2. The antiviral material of claim 1, wherein the cationic polymer is selected from the group consisting of PEI, linear polyethyleneimine, branched polyethyleneimine, gelatin, chitosan, cationic peptides, cationic cyclodextrin, cationic dextran, cationic cellulose, polylysine, polyamidoamine, poly(amino-co-ester) or poly[2-(N,N-dimethylamino)ethyl methacrylate]polyethylenimine.
3. 3. The antiviral material of claim 2, wherein the cationic polymer is polyethyleneimine.
4. 4. The antiviral material of claim 3, wherein the space charge electret material comprises 0.195% to 10% polyethyleneimine cationic polymer.
5. 5. The antiviral material of claim 4, wherein the space charge electret material comprises substantially 2% to 8% polyethyleneimine cationic polymer.
6. 10. The hydrophobic material of claim 1, wherein the hydrophobic substrate material is one or more of cotton-polyester blends, cotton, polyester, cellulose-polyester blends, cellulose, spunlace, polypropylene (PP), polylactic acid (PLA), polyethylene (PE), polyvinyl chloride (PVC), acrylonitrile butadiene styrene (ABS), poly(methyl methacrylate) (PMMA), polytetrafluoroethylene (PTFE), silicone, latex, nylon, or glass.
7. 6. The hydrophobic material of claim 5, wherein the hydrophobic substrate material is one or more of a cotton-polyester blend, cotton, polyester, cellulose, polypropylene, polyethylene, or spunlace.
8. The material has a resistance of 2 to 35 nC cm -2 2. The antiviral material of claim 1, having a minimum average positive surface charge of
9. 10. The antiviral material of claim 1, wherein the material retains its antiviral effectiveness by being woven, bonded, blended or mixed in a volume with other non-antiviral materials.
10. 10. The antiviral material of claim 1, wherein the material is formed as a porous sheet, membrane, woven or nonwoven fabric.
11. 1. A method for producing an antiviral material, comprising: Dissolving the space charge electret material in a suitable solvent to form a space charge electret material / solvent mixture, the concentration of the space charge electret material in the solvent being between 0.195% and 10%; applying the space charge electret material / solvent mixture to a hydrophobic substrate material by dip coating and / or spraying to coat the hydrophobic substrate material; subjecting the resulting coated hydrophobic material to a tension forming process, the tension forming process including one or more of steaming, heating, applying pressure and / or applying pressure and washing the material to remove unbound mixture components; The method includes:
12. The method of claim 11 , wherein the space charge electret material is dissolved in a solvent that does not have any added salt.
13. The method of claim 12, wherein the solvent is water.
14. The method of claim 11, wherein the space charge electret material is 0.195% to 10% polyethyleneimine.
15. The method of claim 14, wherein the space charge electret material is substantially 2% to 8% polyethyleneimine.
16. 12. The method of claim 11, wherein the space charge electret material / solvent mixture is uniformly applied to a hydrophobic substrate material to form a polymer-impregnated substrate material, and the polymer-impregnated substrate is heated at 50-160° C. for at least 5 seconds.
17. 12. The method of claim 11, wherein the hydrophobic substrate material is one or more of cotton-polyester blends, cotton, polyester, cellulose-polyester blends, cellulose, spunlace, polypropylene (PP), polylactic acid (PLA), polyethylene (PE), polyvinyl chloride (PVC), acrylonitrile butadiene styrene (ABS), poly(methyl methacrylate) (PMMA), polytetrafluoroethylene (PTFE), silicone, latex, nylon, or glass.
18. 18. The method of claim 17, wherein the hydrophobic substrate material is one or more of a cotton-polyester blend, cotton, polyester, cellulose, or spunlace.
19. The resulting coated hydrophobic material has a hydrophobicity of 2–35 nC cm -2 12. The method of claim 11, wherein the surface has a minimum average positive surface charge of
20. The method of claim 11 , wherein the material is formed as a porous sheet, membrane, woven or nonwoven fabric.